BM ERI - SR-TYPE VARIABLE STAR - Brukhanov, I. S. (Одеські астрономічні публікації, 2017)
Based on 218 negatives from the Odessa plate collection, BM Eri is classified as an SRa-type star with a 565.d5 period; range in pv 6.m9 - 8.m5; spectrum gM6; more probable minimuma at JD 2439042, 2440183.4, 2446475.